The Impact of Social Media on Political Engagement Among Urban and Rural Youth - Noviyantho, Rino; Dasmawati, Andi; Hartawati, Hartawati (Journal Social Civilecial, 2024)
The present quantitative study examines how social media affects youth political engagement between urban-based and rural-based participants. Data acquisition occurred through surveys directed at 500 youth participants ranging from 18 to 24 years old who resided in urban as well as rural areas. Urban young participants demonstrated higher levels of political participation than young people in rural areas. The study discovered through its results that social media usage duration enhances political participation among young people. The available social media tools which urban fixated youths used for political discussions included Facebook and Instagram but rural youths expressed limited interaction because these platforms lack accessibility. This study addresses existing literature gaps about geographic variations of youth political activism to demonstrate why rural youth need higher digital literacy and their political activity levels increased. The conclusions offer different approaches that enhance political activism through increased use of social media recommendations in both city and country areas. The findings from this study will be beneficial for those in education and policymaking who wish to improve youth political participation via social media.